Effect of Soaking and Boiling Time on the Functional Properties of Jack Bean Flour - William Indra Tandjung; Anita Maya Sutedja; Susana Ristiarini; Chatarina Yayuk Trisnawati (Food ScienTech Journal, 2024)
Jack bean is a type of legume that is widely cultivated in Indonesia, but its use is still limited. The levels of protein and carbohydrates contained in the bean have the potential to be developed, so it is necessary to know its functional properties. The bean has a hard texture; therefore, it needs to be pre-treated by soaking and boiling. Soaking causes the structure of the bean to become soft due to the imbibition of water into the cells. Boiling causes starch gelatinization and protein hydrolysis. This study aimed to determine the profile of the functional properties of jack bean flour with variations in soaking and boiling time. The soaking times studied were 6, 12, and 24 h and the boiling times studied were 5, 10, and 15 min. Each treatment level was replicated three times. Data obtained were calculated the mean and standard deviation to determine and analyze jack bean flour functional properties profile. The results showed that soaking and boiling time increased moisture content, water absorption, oil absorption, emulsion stability, and foam stability, while protein solubility, emulsion capacity, and foam capacity decreased. Good emulsion stability after 4 h of storage was provided from 24 h of soaking time and 15 min of boiling time combination. The jack bean flour had potential emulsification properties which potential to be applied to emulsion-based products.